G3 sports supplement in short triathlon: improvements in training, performance, recovery and oxidative stress - Belcaro, G.; Hu, S.; Strong, J.; Feragalli, B.; Vinciguerra, G.; Cacchio, M.; Ce, M. R. (Minerva Medica, 2018)
BACKGROUND: This registry study evaluated the effects of G3 Sports supplement drink (G3) on performance and endurance in triathlon in amateur athletes in a period of 2 weeks of training. G3 is composed of a proprietary fruit juice blend high in carotenoid compounds as well as 100 mg of standardized French oak (Quercus robur) wood extract, Robuvit®, per 50 mL bottle. The antioxidant and anti-inflammatory actions of the compounds in G3 may improve training efficiency (decreasing post-triathlon muscular pain, cramps and improve recovery time) and decrease post-training plasma free radicals (PFR). METHODS: We selected 50 healthy subjects available to follow the registry plan (age 30-40). No clinical or risk condition were present; no medications were used. Subjects followed a free diet. None used sport supplements (aminoacids or anabolic products). The use of rehydrating drink (Polase) was suggested to all subjects. The only other admitted beverage was Gatorade for use by the control group only. Triathlon total time as well as objective markers of oxidative stress, measured as plasma concentration of free radicals (PFR), and intravascular hemolysis (hemoglobin, serum ferritin, unconjugated bilirubin (UBR) and lactate dehydrogenase (LDH) were measured. RESULTS: Fifty subjects were included: 25 using the supplement; 25 subjects did not use the supplement and acted as controls. Routine blood tests were normal at inclusion and after the final triathlon. The two groups were comparable considering men and women performances at inclusion and age distribution. Drinking and training regimens were comparable between the groups. No side effects or tolerance problems were reported; all G3 drinks were used as indicated. The final "measurement" run was not competitive but chronometric. All subjects completed the test. All subjects performances improved with training. The improvements were seen in parallel both in men and women. The improvement was significantly greater with G3 (P<0.05). The final variation in time was superior with G3 vs. controls (P<0.05). Oxidative stress (PFR), assessed 1 h after the final run, was higher in controls (P<0.05). The higher level of PFR may be associated to a slower recovery time after training and after the test run. After the final test run triathlon, there were no significant changes in hemoglobin or serum ferritin in both groups. Athletes using G3 had a lower variation in UBR and LDH; however, both were significantly increased in controls (P<0.05). CONCLUSIONS: G3 supplementation significantly improved exercise performance in two weeks training time and appeared to significantly decrease oxidative stress and hemolysis resulting from exercise.